2018
DOI: 10.18203/2394-6040.ijcmph20181379
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and perception of tuberculosis management among tuberculosis-infected patients in resource constraint setting: field experience from Oyo state, South-West, Nigeria

Abstract: Background: Inadequate knowledge and misconceptions about tuberculosis (TB) contribute to the burden of the disease by influencing patients' behavior and attitude towards the disease and undermining infection control efforts. This study assesses the level of knowledge, attitude and perception of TB and its management among TB-infected patients. Methods: A descriptive cross-sectional was used to interview 712 TB patients using a semi-structured questionnaire between June and October 2016. Bivariate and multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
2
4
0
1
Order By: Relevance
“…As a result, they did not visit the health center and tended to delay the health-seeking behaviour. These findings are consistent with other studies [16,17,18].…”
Section: Discussionsupporting
confidence: 94%
“…As a result, they did not visit the health center and tended to delay the health-seeking behaviour. These findings are consistent with other studies [16,17,18].…”
Section: Discussionsupporting
confidence: 94%
“…This demonstrates that patients with tuberculosis may not have been getting relevant and reliable health information to satisfy their health information needs, thus implying that many of the patients are likely to have an information gap. This outcome supported the finding of Oladimeji et al [23] done in Nigeria, who found that their respondents (TB patients) could not fully assimilate the information given by the health care providers. Hence, a high proportion of poor perception of TB illness among them.…”
Section: Discussionsupporting
confidence: 88%
“…The inadequate screening for COVID-19 could be attributed to the unavailability of proximal testing equipment and centres as is currently seen in the country. For these two diseases, the fear of being stigmatized, even at the facility level, may prompt clients to decline providing answers to questions related to the diseases thereby making screening difficult for health workers [21].…”
Section: Discussionmentioning
confidence: 99%